Profil Industri Mebel Di Kelurahan Pasia Nan Tigo Kecamatan Koto Tangah Kota Padang - rizkamdial aris; fitriana Syahar (JURNAL BUANA, 2019)
The purpose of this study is (1) Learn about the profile of the furniture industry specifically on production factors in terms of capital, raw materials and labor. (2) Knowing the obstacles faced by industry. (3) Knowing the range of services area and marketing of the furniture industry. The method that used in this study is a Quantitative Descriptive method. Data collection methods used were questionnaires and research documentation. The data analysis technique used (1) descriptive data analysis (2) analysis of service area using buffer. Research result shows that the profile of the furniture industry in the production factors seen in terms of capital, raw materials and labor in Pasia Nan Tigo Village is only one industry that has capital constraints. In the case of raw materials, industry owners state that the raw material is still sufficient in the production process. The furniture industry owner also stated that the number of permanent workers is still insufficient. Furniture industry in Pasia Nan Tigo Village is included in the small and medium industry. The obstacles faced by the furniture industry in the production factors are capital, raw materials and labor. From the capital factor, the obstacles faced by furniture industry owners are large-scale production which still requires additional capital. In the case of raw materials the obstacles faced by the owners of the furniture industry are the distance from the origin of raw materials. In the range of services area, the furniture industry in Pasia Nan Tigo Village is on average within the province.